Walt Whitman. - Chase, Richard Volney, 1914-1962 (University of Minnesota pamphlets on American writers, 1961)
Walt Whitman - American Writers 9 was first published in 1961. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.